Factors Affecting Perfection and Quality of Work (Itqan) Applied Study on Workers who belong to Shaqra University, College of Science and Humanities, Thadiq Branch, KSA - Farg, Mohamed Hassan Mahmoud; Khalil, Faiza Mohamed Hassan; Salih, Hafiz Ibrahim (International Journal of Social Sciences and Management, 2017)
This study mainly focused on the factors that affect the Itqan or the perfection of any work. The paper depends on a simple random sample of size 211 items. A questionnaire of 26 variables or question was used to collect data from employee and students of the faculty of science and humanities, Shaqra university, KSA during may 2016. In the results, there are 6 factors affecting the Itqan (perfection). These factors are creative and administrative, environmental, The spiritual, incentives, Administrative factor and combined factor respectively. Int. J. Soc. Sc. Manage. Vol. 4, Issue-2: 127-136